Fluid circulation and carbonate vein precipitation in the footwall of an oceanic core complex, Ocean Drilling Program Site 175, Mid‐Atlantic Ridge. (30th October 2015) - Schroeder, Tim; Bach, Wolfgang; Jöns, Niels; Jöns, Svenja; Monien, Patrick; Klügel, Andreas
Abstract: Carbonate veins recovered from the mafic/ultramafic footwall of an oceanic detachment fault on the Mid‐Atlantic Ridge record multiple episodes of fluid movement through the detachment and secondary faults. High‐temperature (∼75–175°C) calcite veins with elevated REE contents and strong positive Eu‐anomalies record the mixing of up‐welling hydrothermal fluids with infiltrating seawater. Carbonate precipitation is most prominent in olivine‐rich troctolite, which also display a much higher degree of greenschist and sub‐greenschist alteration relative to gabbro and diabase. Low‐temperature calcite and aragonite veins likely precipitated from oxidizing seawater that infiltrated the detachment fault and/or within secondary faults late or post footwall denudation. Oxygen and carbon isotopes lie on a mixing line between seawater and Logatchev‐like hydrothermal fluids, but precipitation temperatures are cooler than would be expected for isenthalpic mixing, suggesting conductive cooling during upward flow. There is no depth dependence of vein precipitation temperature, indicating effective cooling of the footwall via seawater infiltration through fault zones. One sample contains textural evidence of low‐temperature, seawater‐signature veins being cut by high‐temperature, hydrothermal‐signature veins. This indicates temporal variability in the fluid mixing, possibly caused by deformation‐induced porosity changes or dike intrusion. The strong correlation between carbonate precipitation and olivine‐rich troctolites suggests that the presence of unaltered olivine is a key requirement for carbonate precipitation from seawater and hydrothermal fluids. Our results also suggest that calcite‐talc alteration of troctolites may be a more efficient CO2 trap than serpentinized peridotite. Key Points: Carbonate veins record fluid flow through an oceanic core complex footwall Carbonate precipitation is strongly correlated with nonserpentinized olivine Distinct carbonate vein generations record variations fluid flow and mixing